Synthesis and Evaluation of Conjugates of Novel TLR7 Inert Ligands as Self-Adjuvanting Immunopotentiators - Gao, Dong (ACS Med Chem Lett, 2015)
[Image: see text] During the design and synthesis of a series of 8-hydroxy-2-(2-methoxyethoxy)-adenine derivatives bearing various substituted −RCOOH groups at the 9-position, we identified a TLR7-inert ligand, which does not activate TLR7 signaling pathway. Of interest, the coupling of weakly immunogenic antigens via the −RCOOH group was able to significantly enhance the immunogenicity of the antigens. Herein, an inert ligand, 9-(3-carboxypropyl)-8-hydroxy-2-(2-methoxyethoxy)-adenine (5, GD2), was synthesized and conjugated to 5 different weakly immunogenic antigens (BSA, OVA, MSA, MG7, and thymosin). Compared with the GD2 and the potent agonist UC-1 V150, all conjugates demonstrated potent immunogenicity in vitro and in vivo. All conjugates induced prolonged increases, while UC-1 V150 showed a rapid decline in the levels of proinflammatory cytokines following initial increases. These data indicate that the immunostimulatory activity of TLR7-inert ligands could be amplified and prolonged by conjugation to antigens, thus broadening the potential therapeutic application of these agents.